Preparation method of continuous graphene nanofiber bundle
Through near-field electrospinning, multi-stage combined drafting, Lys-Dopa bath and high-temperature graphitization treatment, problems such as low tensile strength and poor mechanical strength in the preparation of graphene fibers are solved, and the high performance improvement of graphene fibers is achieved and suitable for large-scale production.
Patent Information
- Application Number
- CN202411719188.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
The existing preparation process of graphene fibers has problems such as low tensile strength, inappropriate large-scale production, poor mechanical strength and high cost, and it is difficult to achieve the mechanical and thermoelectric properties of graphene fibers that theoretically surpass industrial carbon fibers.
Graphene fibers are prepared by near-field electrospinning and multi-stage joint drafting process. The viscoelasticity of the spinning liquid is improved by adding plasticizers, and the wrinkles inside the fiber are improved by Lys-Dopa bath, and the plasticizer is removed by high-temperature graphitization treatment to improve the mechanical properties of the fibers.
The high tensile strength and mechanical properties of graphene fibers are improved, structural defects are reduced, orientation degree and overall performance of fibers are improved, and the process is simple and easy to implement, suitable for continuous and automated production.
Smart Images

Figure CN119553392A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of graphene fiber materials, and in particular to a method for preparing a continuous graphene nanofiber bundle. Background Art
[0002] Carbon fiber materials are widely used in defense, aerospace, sports equipment and other fields due to their light weight, fatigue resistance, excellent mechanical strength and heat / electrical transmission performance. The current industrial carbon fiber is generally obtained by carbonizing / graphitizing precursor viscose, asphalt or polyacrylonitrile. The basic constituent unit of the carbon fiber obtained by this method is microcrystalline graphite with a diameter of less than 20nm. Due to the large number of grain boundaries, its actual density and strength do not reach the theoretical value (actual: 1.80g / cm 3 , 7GPa; theory: 2.266g / cm 3 , 180GPa), and its thermal / electrical transport performance is also relatively limited. Graphene, as a two-dimensional hexagonal single layer sp 2 Hybridized carbon atoms form large sheets of material with sizes of several microns or even tens of microns, and have excellent mechanical properties (strength ~130GPa, modulus 1.1TPa), electrical properties (conductivity 108S / m, carrier mobility 200000cm 2 / V / s, current carrying capacity 1~2GA / cm 2 ), thermal properties (thermal conductivity 5300W / (m·K)) and excellent stability. If it is assembled from nanosheets into macroscopic graphene fibers, carbon-based fibers with larger crystalline graphite structures can be obtained, it is expected that its excellent mechanical, electrical and thermal properties at the nanoscale will be inherited to the macroscale, thus breaking through the limited mechanical strength and thermoelectric properties of existing industrial carbon fibers.
[0003] Since it is difficult to find a suitable solvent to disperse graphene itself and form a spinning solution with the required concentration for spinning, graphene fibers usually use graphene oxide (GO) as a precursor that can be dispersed in water and other common solvents and can form a liquid crystal phase. After spinning, graphene fibers are obtained through a reduction process. At present, the preparation processes of graphene fibers mainly include wet spinning, dry spinning, hydrothermal reduction assembly, film winding, template-assisted CVD, etc. Among them, the surface of graphene fibers obtained by dry spinning has more micropores due to solvent evaporation, resulting in low tensile strength; hydrothermal reduction assembly is not suitable for large-scale production of graphene fibers due to the limited length of the capillary and the long reaction time; the graphene fibers obtained by the film winding method have poor mechanical strength, and the CVD method has a high cost and is not suitable for large-scale production. Relatively speaking, using the pre-arranged orientation of GO liquid crystals and drawing on the wet spinning method of traditional polymer materials is the mainstream method for preparing graphene fibers at present, and it is most likely to achieve mass production.
[0004] Since Xu et al. first used liquid crystal GO to produce graphene fibers with a tensile strength of 140 MPa and a Young's modulus of 7.7 GPa in the literature Graphene chiral liquid crystals and macroscopic assembled fibres in 2011, a large number of scholars have been committed to improving and optimizing the spinning process, continuously making breakthroughs and improving graphene fibers with better mechanical, electrical, thermal and other properties, in order to achieve the mechanical and thermoelectric properties of graphene fibers that theoretically surpass those of industrial carbon fibers.
[0005] After investigation, it was found that the strength of graphene fiber is mainly affected by the parameters such as the size of the precursor GO, the regularity of the lamellae, the degree of orientation, and the interface interaction. Among them, the larger the size of GO, the greater the liquid crystal tendency and the more obvious the pre-orientation arrangement, which brings higher strength and modulus to the graphene fiber; in addition, the increase in the size of GO is also conducive to reducing the number of defect sites, thereby improving the strength of the graphene fiber. Xiang et al. compared the mechanical properties of graphene fibers spun from 20μm and 9μm GO in the literature Large Flake Graphene Oxide Fibers with Unconventional 100% Knot Efficiency and Highly Aligned Small Flake Graphene Oxide Fibers and found that the graphene fibers spun from large-sized GO have 78% higher strength, 88% higher elastic modulus, and 178% higher elongation at break than those from small-sized GO. However, although large-sized GO can improve the strength of graphene fibers, it will cause the sheets to curl and produce micropores. This adverse effect on the regularity of the sheets affects the further improvement of the mechanical properties of the fibers. Therefore, the document Highly thermally conductive and mechanically strong graphene fibers. Science records that on the basis of large-sheet GO, small-sheet GO is used to fill the former to produce micropores and gaps, thereby increasing the mechanical strength of the fiber to 1.08GPa.
[0006] Since the study found that graphene fibers are similar to chemical fibers, the higher the orientation degree of the sheets along the fiber axis, the greater the strength and modulus of the fibers. Therefore, some researchers have proposed a method to simultaneously remove GO wrinkles and improve GO orientation. Xin et al. mentioned in the literature Microfluidics-enabled orientation and microstructure control of macroscopic graphene fibres that the directional control of GO microfluidics was achieved through the special design of the spinning liquid flow channel, and obtained graphene fibers with an orientation degree of 0.94, dense and non-microporous, with a strength of up to 1.9±0.1GPa and a modulus of 309±16GPa. Li et al. inserted an appropriate amount of plasticizer to achieve the post-stretching of GO fibers in the literature Highly Crystalline Graphene Fibers with Superior Strength and Conductivities by Plasticization Spinning, and obtained graphene fibers with an orientation degree of 0.97 and a strength of up to 3.4±0.07GPa after graphitization. In addition, since graphene sheets are prone to slippage, enhancing the interaction between graphene sheets is also an effective method to improve the mechanical properties of graphene fibers. Xu et al. used Ca 2+ Cross-linking GO carboxyl groups and using ionic bonds to enhance the interaction of graphene sheets improves the strength of graphene fibers. Currently, the highest tensile strength and elastic modulus of graphene fibers are 3.4 GPa and 341.7 GPa, while the highest tensile strength and elastic modulus of carbon fibers are 7.15 GPa and 600 GPa. The mechanical properties of graphene fibers, which should theoretically be stronger than those of carbon fibers, are still far from being achieved. Therefore, the preparation process of graphene fibers still needs to be further optimized, and attempts should be made to find other ways to improve the performance of graphene fibers. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing a continuous graphene nanofiber bundle, thereby providing a new idea for the preparation process of graphene fibers.
[0008] To achieve the above object, the present invention provides the following technical solution: a method for preparing a continuous graphene nanofiber bundle, comprising the following specific steps:
[0009] S1. Preparation of spinning solution: preparing and formulating graphene oxide nanoribbon solution, and adding a plasticizer to obtain a spinning solution;
[0010] S2 Near-field electrospinning and multi-stage combined drawing: The spinning solution is injected into the electrospinning device through a spinneret of 0.2-1 mm. After near-field electrospinning and air solidification, it is solidified in a coagulation bath to obtain basic graphene oxide fibers; multiple fibers are assembled into nanofiber multifilaments in a coagulation bath under the guidance of a glass rod and then enter the subsequent multi-stage combined drawing process. By adjusting the number of drawing stages and the drawing ratio of each stage, GO wrinkles can be removed and the orientation degree can be improved to obtain a GO fiber aggregate;
[0011] S3 Lysine-dopamine (Lys-Dopa) bath: immerse the GO fiber assembly in the Lys-Dopa solution, adjust the concentration and reaction time of the Lys-Dopa solution, improve the wrinkles inside the GO fiber, and finally collect it through the twisting process;
[0012] S4 reduction process: The collected GO fibers are reduced with hydroiodic acid to obtain reduced graphene fibers, followed by high-temperature graphitization treatment to restore the atomic defects on GO and generate graphite crystals, and to pyrolyze Lys-Dopa into a nitrogen-rich graphite structure. At the same time, the plasticizer is removed, and the graphene nanofiber bundle product is obtained after graphitization treatment.
[0013] Preferably, in the above step S1, the concentration of the graphene oxide nanoribbon solution is 5-15 g / L, the length of the graphene nanoribbon is 3-10 μm, the width is 50-100 nm, and the plasticizer is sodium polyacrylate, and the concentration after addition is 0.1-0.5 g / L.
[0014] Preferably, in the above step S2, the electrospinning uses a 10mL syringe as an electrospinning liquid reservoir, uses 3 to 8 stainless steel injection needles with a specification of 20 to 30G, and simultaneously prepares 3 to 8 graphene fibers to form multifilaments. The flow rate of the electrospinning liquid is controlled by a microinjection pump, and a flat plate is used to receive the fibers; there is a circle of auxiliary electrodes outside the injection needles to control the electric field interference between different needles, thereby reducing the instability of the GO fibers during the stretching process under the electric field force, and the voltage of the auxiliary electrodes is 10 to 30 kV.
[0015] Preferably, the electrospinning process parameters in the above step S2 include: a propulsion rate of 0.5 to 4 mL / h, a voltage of 10 to 30 kV, a distance between the needle and the surface of the coagulation bath of 0.5 to 5 cm, a spinning time of 0.1 to 2 h, and always maintaining 3 to 8 fibers continuously and stably deposited in the coagulation bath under the action of the electric field force, and the coagulation liquid is a 5 to 10 wt% CaCl2 solution.
[0016] Preferably, in the above step S2, the number of drafting stages of the multi-stage combined drafting is 2 to 5, and the drafting speed of the drafting roller is 10 to 30 cm / min.
[0017] Preferably, in the above step S3, the concentration of the Lys-Dopa solution is 1 to 5 mg / ml, and the reaction time is 1 to 3 h.
[0018] Preferably, in the above step S4, the hydroiodic acid reduction is carried out at 90° C. for 12 h.
[0019] Preferably, in the above step S4, the graphitization treatment condition is to heat to 3000° C. at a rate of 10° C. / min in an argon flow and maintain for one hour.
[0020] Another technical solution provided by the present invention is a method for preparing a continuous graphene nanofiber bundle, comprising the step of immersing in a Lys-Dopa solution after a coagulation bath, and / or the step of twisting a plurality of graphene fibers into bundles before reducing them into graphene fibers.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The preparation method of the continuous graphene nanofiber bundle uses GO nanobelts as raw materials, and replaces the sheet winding molding of the nanographene fiber cross section with stacking molding by changing the aspect ratio of the GO sheet, thereby removing radial wrinkles and pores in the graphene fiber that are difficult to remove by axial stretching, and further improving the strength of the fiber; the added plasticizer can increase the viscoelasticity of the spinning solution, so that it can be stretched and refined by electrostatic force during the spinning process.
[0023] 2. The preparation method of the continuous graphene nanofiber bundle adopts near-field electrospinning, which can avoid the unstable whipping motion in the traditional electrospinning process by taking advantage of the controllable electric field force that traditional electrospinning does not have, and the extensibility provided by the stretching combined with a small amount of plasticizer, combined with a multi-stage stretching strategy, thereby obtaining continuous, stable and controllable nano GO fibers. This method is beneficial to reducing structural defects, improving orientation, and improving the strength of graphene fibers.
[0024] 3. The preparation method of the continuous graphene nanofiber bundle adopts a Lys-Dopa bath to further treat the graphene fibers, and cooperates with the adhesion effect produced by the hydrogen bonds of Dopa and the π-π interaction between catechol and GO sheets to produce a strong binding effect between the GO sheets. The positively charged lysine and the negatively charged graphene oxide repel each other and form ionic crosslinks. The graphene oxide becomes tighter and tighter under the action of the repulsive force, which greatly improves the mechanical strength of the graphene fiber.
[0025] 4. The method for preparing the continuous graphene nanofiber bundle is to twist a plurality of graphene fibers that have passed through a Lys-Dopa bath into a bundle. Since Lys-Dopa has wet adhesion, the graphene fibers are tightly connected after twisting, which is more conducive to improving the mechanical properties of the product.
[0026] 5. The method for preparing the continuous graphene nanofiber bundle can remove the plasticizer in the final graphitization process to maintain the integrity of the graphene fiber crystal structure. At the same time, Lys-Dopa can be converted into a nitrogen-rich graphite structure after pyrolysis, which can enhance the bonding force without damaging the electrical properties.
[0027] 6. The method for preparing the continuous graphene nanofiber bundle has simple steps and is easy to realize continuous automated production, and can produce graphene nanofiber bundle products with high tensile strength, while providing new process steps for reference for the future development of the graphene fiber field. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a SEM image of the graphene fiber bundle prepared in Example 1, and the illustration is 20 microns;
[0029] Figure 2 This is a real knotting diagram of the graphene fiber bundle of Example 1;
[0030] Figure 3 This is a SEM image of a single graphene fiber prepared in Comparative Example 1, and the illustration is 1 micron;
[0031] Figure 4 This is the SEM image of the graphene fiber bundle prepared in Comparative Example 2, and the illustration is 10 microns. DETAILED DESCRIPTION
[0032] A method for preparing a continuous graphene nanofiber bundle comprises the following specific steps:
[0033] S1. Preparation of spinning solution: preparing and preparing a graphene oxide nanoribbon solution, and adding a plasticizer to obtain a spinning solution; for reference, the concentration of the graphene oxide nanoribbon solution can be 5-15 g / L, the length of the graphene nanoribbon can be further selected to be 3-10 μm, and the width can be further selected to be 50-100 nm. The plasticizer can be sodium polyacrylate, and the concentration after addition is preferably controlled at 0.1-0.5 g / L;
[0034] S2 Near-field electrospinning and multi-stage combined drawing: The spinning solution is injected into the electrospinning device through a spinneret of 0.2-1 mm. After near-field electrospinning and air curing, it is cured in a coagulation bath to obtain basic graphene oxide fibers; multiple fibers are assembled into nanofiber multifilaments in a coagulation bath under the guidance of a glass rod and then enter the subsequent multi-stage combined drawing process. By adjusting the number of drawing stages and the drawing ratio of each stage, the GO wrinkles can be removed and the orientation degree can be improved (for reference, the drawing ratio is controlled by the drawing speed ratio of the drawing roller, and multi-stage progressive drawing is used to maintain the continuity of the fiber without breaking. After each stage of drawing, the fiber enters a deionized water bath to release the excess stress concentration on the fiber to further reduce the probability of fiber breakage. Oriented drawing is a well-known technology in the art, so it will not be repeated here), and a GO fiber aggregate is obtained. For reference, the number of drawing stages of the multi-stage combined drawing can be 2-5, and the drawing speed of the drawing roller can be controlled at 10-30 cm / min;
[0035] In an optional embodiment, electrospinning uses a 10mL syringe as an electrospinning liquid reservoir, uses 3 to 8 stainless steel injection needles with a specification of 20 to 30G, and simultaneously prepares 3 to 8 graphene fibers to form multifilaments. The flow rate of the electrospinning liquid is controlled by a microinjection pump, and a flat plate is used to receive the fibers. There is a circle of auxiliary electrodes outside the injection needles to control the electric field interference between different needles, thereby reducing the instability of the GO fibers during the stretching process under the electric field force, and the voltage of the auxiliary electrodes is 10 to 30 kV.
[0036] For reference, the electrospinning process parameters include: a propulsion rate of 0.5-4 mL / h, a voltage of 10-30 kV, a distance between the needle and the surface of the coagulation bath of 0.5-5 cm, a spinning time of 0.1-2 h, and always maintaining 3-8 fibers continuously and stably deposited into the coagulation bath under the action of the electric field force, and the coagulation liquid is a 5-10 wt% CaCl2 solution; the electrospinning process is a mature technology in this field, so it is only used for reference here, and it is not necessary to be within this range. The electrospinning process parameters that are known in the art to be beneficial to the production of graphene fibers are applicable.
[0037] The present invention adopts the benefit of near-field electrostatic spinning as follows: the graphene oxide spinning solution is drawn by the drawing force of the electrostatic field force, and its fiber is reduced from the micron level of wet spinning to the nanometer level, so that the diameter size of the graphene fiber is fine-deniered by two to three orders of magnitude, so as to significantly reduce the internal structural defects of the graphene fiber, in order to achieve the leap-forward growth of the strength of the graphene fiber. Wherein a small amount of ultra-high molecular weight plasticizer is added to the GO spinning solution, and the viscoelasticity of the GO spinning solution is given, and the electrostatic force can be pulled and stretched to be thinned during the spinning process, and a small amount of high molecular weight ultra-high molecular weight plasticizer can be removed in the subsequent thermal annealing process, and the integrity of the crystal structure of the graphene fiber is maintained. Simultaneously, the near-field electrostatic spinning method is used, and the electric field control is coordinated to avoid the unstable whipping motion (the randomness and uncontrollability of the whipping motion can cause the discontinuity and uneven diameter of the nanofiber) of the latter half of the traditional electrostatic spinning method, so as to obtain a continuous, stable and controllable nano GO fiber.
[0038] S3 Lysine-dopamine (Lys-Dopa) bath: immerse the GO fiber assembly in the Lys-Dopa solution, adjust the concentration and reaction time of the Lys-Dopa solution, improve the wrinkles inside the GO fiber, and finally collect it through the twisting process (the specific twisting and weaving method can be changed according to needs). Since Lys-Dopa is sticky, each GO fiber is tightly connected when twisted after passing through the Lys-Dopa bath;
[0039] The concentration of the above Lys-Dopa solution can be further preferably 1-5 mg / ml, and the reaction time can be further preferably 1-3 h. The concentration and time can be adjusted according to actual production, and even multiple pools of Lys-Dopa baths can be used for different concentrations and different times.
[0040] The surface of the GO sheet itself has a strong negative charge (Zeta potential -61±5mV). Therefore, the adhesion effect produced by Dopa hydrogen bonding and the π-π interaction between catechol and GO sheets produces a strong binding effect between the GO sheets. The positively charged lysine and the negatively charged graphene oxide repel each other and form ionic crosslinks. The graphene oxide becomes tighter and tighter under the action of repulsive force, which greatly improves the mechanical strength of the graphene fiber.
[0041] S4 reduction process: the collected GO fibers are reduced with hydroiodic acid to obtain reduced graphene fibers. For reference, the reduction can be carried out at 90°C for 12 hours; followed by high-temperature graphitization treatment. For reference, the conditions for the graphitization treatment can be heated to 3000°C at a rate of 10°C / min in an argon gas flow and maintained for one hour. After the graphitization treatment, a graphene nanofiber bundle product is obtained; the above hydroiodic acid reduction and high-temperature graphitization treatment conditions are not necessarily required under these conditions, as long as they are the graphene fiber reduction conditions and graphitization treatment conditions recognized in the art. Among them, the preferred graphitization treatment is suitable for restoring the atomic defects on GO and generating graphite crystallites, and pyrolyzing Lys-Dopa into a nitrogen-rich graphite structure, while removing the plasticizer. Lysine-polydopamine can be converted into a nitrogen-rich graphite structure after pyrolysis, while improving the bonding strength between graphene sheets, it will not affect the electrical properties of the graphene fibers. If the pyrolysis is not complete, the mechanical properties of the graphene fibers will not be reduced.
[0042] The present invention is further described below through several embodiments and comparative examples. It should be clear that the following are only a small number of embodiments of the present invention, so they should not be used as absolute limitations of the present invention. The key to the present invention lies in the various process steps. In the embodiments and comparative examples, the same graphene nanoribbon raw material is used, and its length range is 3 to 10 μm and the width range is 50 to 100 nm, but it does not mean that this nanoribbon must be used to use the present invention.
[0043] Embodiment 1
[0044] First, the spinning solution (graphene nanoribbon concentration is 10g / L, PAS concentration is 0.2g / L) is prepared, and then the spinning solution is injected into the electrospinning device through a 0.5mm spinneret. Among them, the electrospinning uses a 10mL syringe as the electrospinning solution reservoir, and uses 4 stainless steel injection needles with a specification of 25G (there is a circle of auxiliary electrodes with a voltage of 10kV outside the needle to control the electric field interference between different needles), the needle advancement rate is 1mL / h, the voltage is 20kV, the distance between the needle and the coagulation bath surface is 3cm, and the spinning time is 1h. After near-field electrospinning and air curing, the fibers are continuously and stably drawn and deposited into a coagulation bath of 5wt% CaCl2 solution under the action of the electric field force to solidify and form, and then the fibers are pulled into the drawing and twisting instrument through a glass rod for a 3-stage drawing process, and the drawing speeds of the drawing rollers are 10cm / min, 12cm / min, and 14cm / min respectively. After the drawing is completed, the fiber bundle is collected by twisting process, and the fiber bundle is immersed in 1mg / ml Lys-Dopa solution for reaction for 1h. After the reaction is completed, the GO fiber bundle is collected on a winding roller and reduced with hydroiodic acid (HI) at 90℃ for 12h to obtain reduced graphene fiber, which is then heated to 3000℃ at a rate of 10℃ / min in an argon flow and maintained for one hour to remove the plasticizer, and finally a graphene nanofiber bundle is obtained. The tensile strength of the graphene nanofiber bundle is 2.1GPa as tested by a material testing machine. Figure 1 As shown, SEM observation revealed that the diameter of the graphene nanofiber bundle was about 8 microns.
[0045] Embodiment 2
[0046] First, the spinning solution (graphene nanoribbon concentration is 15g / L, PAS concentration is 0.5g / L) is prepared, and then the spinning solution is injected into the electrospinning device through a 0.2mm spinneret. Among them, the electrospinning uses a 10mL syringe as the electrospinning solution reservoir, and uses 4 stainless steel injection needles with a specification of 30G (there is a circle of auxiliary electrodes with a voltage of 10kV outside the needle to control the electric field interference between different needles), the needle advancement rate is 0.5mL / h, the voltage is 25kV, the distance between the needle and the coagulation bath liquid surface is 3cm, and the spinning time is 1.5h. After near-field electrospinning and air curing, the fibers are continuously and stably drawn and deposited into a coagulation bath of 10wt% CaCl2 solution under the action of the electric field force to solidify and form, and then the fibers are pulled into the drawing and twisting instrument through a glass rod for a 4-stage drawing process, and the drawing speeds of the drawing rollers are 10cm / min, 11cm / min, 12cm / min, and 13cm / min respectively. After the drawing is completed, the fiber bundle is collected by twisting process, and the fiber bundle is immersed in 2.5mg / ml Lys-Dopa solution for 1h. After the reaction is completed, the GO fiber bundle is collected on a winding roller and reduced with hydroiodic acid (HI) at 90℃ for 12h to obtain reduced graphene fiber, which is then heated to 3000℃ at a rate of 10℃ / min in an argon flow and maintained for one hour to remove the plasticizer, and finally a graphene nanofiber bundle is obtained. The tensile strength of the graphene nanofiber bundle is 1.7GPa as tested by a material testing machine.
[0047] Embodiment 3
[0048] First, the spinning solution (graphene nanoribbon concentration is 10g / L, PAS concentration is 0.25g / L) is prepared, and then the spinning solution is injected into the electrospinning device through a 0.2mm spinneret. Among them, the electrospinning uses a 10mL syringe as the electrospinning solution reservoir, and uses three stainless steel injection needles with a specification of 30G (there is a circle of auxiliary electrodes with a voltage of 10kV outside the needle to control the electric field interference between different needles), the needle advancement rate is 1mL / h, the voltage is 20kV, the distance between the needle and the coagulation bath liquid surface is 3cm, and the spinning time is 1h. After near-field electrospinning and air curing, the fibers are continuously and stably drawn and deposited into a coagulation bath of 10wt% CaCl2 solution under the action of the electric field force to solidify and form, and then the fibers are pulled into the drawing and twisting instrument through a glass rod for a three-level drawing process, and the drawing speeds of the drawing rollers are 10cm / min, 11cm / min, and 12cm / min respectively. After the drawing is completed, the fiber bundle is collected by twisting process, and the fiber bundle is immersed in 5mg / ml Lys-Dopa solution for 2h. After the reaction is completed, the GO fiber bundle is collected on a winding roller and reduced with hydroiodic acid (HI) at 90℃ for 12h to obtain reduced graphene fiber, which is then heated to 3000℃ at a rate of 10℃ / min in argon gas flow and maintained for one hour to remove the plasticizer, and finally a graphene nanofiber bundle is obtained. The tensile strength of the graphene nanofiber bundle is 1.9GPa as tested by a material testing machine.
[0049] Comparative Example 1:
[0050] First, the spinning solution (graphene nanoribbon concentration is 10g / L, PAS concentration is 0.25g / L) is prepared, and then the spinning solution is injected into the electrospinning device through a 0.2mm spinneret. Among them, the electrospinning uses a 10mL syringe as the electrospinning solution reservoir, a stainless steel injection needle with a specification of 30G, a needle advancement rate of 1mL / h, a voltage of 20kV, a distance between the needle and the coagulation bath surface of 3cm, and a spinning time of 1h. After near-field electrospinning and air curing, the fibers are continuously and stably drawn and deposited into a coagulation bath of 5wt% CaCl2 solution under the action of the electric field force to solidify and form, and then the GO fibers are collected on a winding roller, reduced with hydroiodic acid (HI) at 90°C for 12h to obtain reduced graphene fibers, and then heated to 3000°C at a rate of 10°C / min in an argon gas flow and kept for one hour to remove the plasticizer, and finally graphene nanofibers are obtained. In this comparative example, twisting and Lys-Dopa bath process were not used. The tensile strength of the single graphene nanofiber was 25 MPa as measured by a material testing machine. Figure 3 As shown, the diameter of a single graphene fiber was observed by SEM to be approximately 250 nanometers.
[0051] Comparative Example 2:
[0052] This comparative example adopts the same parameters as Example 1, but does not pass through a Lys-Dopa bath after drawing. Specifically:
[0053] First, the spinning solution (graphene nanoribbon concentration is 10g / L, PAS concentration is 0.2g / L) is prepared, and then the spinning solution is injected into the electrospinning device through a 0.5mm spinneret. Among them, the electrospinning uses a 10mL syringe as the electrospinning solution reservoir, and uses 4 stainless steel injection needles with a specification of 25G (there is a circle of auxiliary electrodes with a voltage of 10kV outside the needle to control the electric field interference between different needles), the needle advancement rate is 1mL / h, the voltage is 20kV, the distance between the needle and the coagulation bath surface is 3cm, and the spinning time is 1h. After near-field electrospinning and air curing, the fibers are continuously and stably drawn and deposited into a coagulation bath of 5wt% CaCl2 solution under the action of the electric field force to solidify and form, and then the fibers are pulled into the drawing and twisting instrument through a glass rod for a 3-stage drawing process, and the drawing speeds of the drawing rollers are 10cm / min, 12cm / min, and 14cm / min respectively. After the drawing is completed, the fiber bundle is collected through the twisting process, and the fiber bundle is collected on a winding roller, and reduced with hydroiodic acid (HI) at 90°C for 12 hours to obtain reduced graphene fibers, which are then heated to 3000°C at a rate of 10°C / min in an argon flow and maintained for one hour to remove the plasticizer, and finally a graphene nanofiber bundle is obtained. The tensile strength of the graphene nanofiber bundle is 0.7 GPa as tested by a material testing machine. Figure 4 As shown, the diameter of the graphene nanofiber bundle was about 4 microns as observed by SEM.
[0054] The products obtained in the above three embodiments have excellent tensile strength. Although comparative example 1 also adopts processes such as graphene nanoribbons and near-field electrospinning, the tensile strength of the obtained product is poor because twisting and Lys-Dopa bath processes are not adopted. In addition, it can be seen from Example 1 and comparative example 2 that the Lys-Dopa bath of the present invention greatly improves the performance of graphene fibers. It can be seen from comparative examples 1 and 2 that twisting is also very beneficial to the improvement of tensile strength. These two process steps are not limited to the raw materials and spinning methods of the graphene fibers, and can obviously be added alone or in combination to other graphene fiber preparation methods to improve the tensile strength of the product.
[0055] The present invention aims to propose a new approach to enhance the mechanical properties of graphene fibers under parallel conditions. The present invention cannot predict how this approach will be combined with other process methods in the future to help graphene fibers achieve ultimate performance. However, since the process steps in the present invention will not ultimately cause damage to the graphene fibers, it can be expected that this method has good process integration and can be added to other processes as a means of enhancing the performance of graphene fiber products. Among them, pyrolysis of Lys-Dopa after bath can also be used as a means of repairing graphene fibers.
[0056] The above are only preferred embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined by the claims.
[0057] The matters not described in detail in the present invention are all known technologies to those skilled in the art.
Claims
1. A method for preparing a continuous graphene nanofiber bundle, characterized in that: The specific steps include: S1. Preparation of spinning solution: preparing and formulating graphene oxide nanoribbon solution, and adding a plasticizer to obtain a spinning solution; S2 Near-field electrospinning and multi-stage combined drawing: The spinning solution is injected into the electrospinning device through a spinneret of 0.2-1 mm. After near-field electrospinning and air solidification, it is solidified in a coagulation bath to obtain basic graphene oxide fibers; multiple fibers are assembled into nanofiber multifilaments in a coagulation bath under the guidance of a glass rod and then enter the subsequent multi-stage combined drawing process. By adjusting the number of drawing stages and the drawing ratio of each stage, GO wrinkles can be removed and the orientation degree can be improved to obtain a GO fiber aggregate; S3 Lysine-dopamine (Lys-Dopa) bath: immerse the GO fiber assembly in the Lys-Dopa solution, adjust the concentration and reaction time of the Lys-Dopa solution, improve the wrinkles inside the GO fiber, and finally collect it through the twisting process; S4 reduction process: The collected GO fibers are reduced with hydroiodic acid to obtain reduced graphene fibers, followed by high-temperature graphitization treatment to restore the atomic defects on GO and generate graphite crystals, and to pyrolyze Lys-Dopa into a nitrogen-rich graphite structure. At the same time, the plasticizer is removed, and the graphene nanofiber bundle product is obtained after graphitization treatment.
2. The method for preparing a continuous graphene nanofiber bundle according to claim 1, characterized in that: In the step S1, the concentration of the graphene oxide nanoribbon solution is 5-15 g / L, the length of the graphene nanoribbon is 3-10 μm, the width is 50-100 nm, and the plasticizer is sodium polyacrylate, and the concentration after addition is 0.1-0.5 g / L.
3. The method for preparing a continuous graphene nanofiber bundle according to claim 1, characterized in that: In the step S2, the electrospinning uses a 10mL syringe as an electrospinning liquid reservoir, uses 3 to 8 stainless steel injection needles with a specification of 20 to 30G, and simultaneously prepares 3 to 8 graphene fibers to form multifilaments. The flow rate of the electrospinning liquid is controlled by a microinjection pump, and a flat plate is used to receive the fibers. There is a circle of auxiliary electrodes outside the injection needles to control the electric field interference between different needles, thereby reducing the instability of the GO fibers during the stretching process under the electric field force, and the voltage of the auxiliary electrodes is 10 to 30 kV.
4. The method for preparing a continuous graphene nanofiber bundle according to claim 1, characterized in that: The electrospinning process parameters in step S2 include: a propulsion rate of 0.5 to 4 mL / h, a voltage of 10 to 30 kV, a distance between the needle and the surface of the coagulation bath of 0.5 to 5 cm, a spinning time of 0.1 to 2 h, and always maintaining 3 to 8 fibers continuously and stably deposited into the coagulation bath under the action of the electric field force, and the coagulation liquid is a 5 to 10 wt% CaCl2 solution.
5. The method for preparing a continuous graphene nanofiber bundle according to claim 1, characterized in that: In the step S2, the number of drafting stages of the multi-stage combined drafting is 2 to 5, and the drafting speed of the drafting roller is 10 to 30 cm / min.
6. The method for preparing a continuous graphene nanofiber bundle according to claim 1, characterized in that: In step S3, the concentration of the Lys-Dopa solution is 1-5 mg / ml, and the reaction time is 1-3 h.
7. The method for preparing a continuous graphene nanofiber bundle according to claim 1, characterized in that: In step S4, the hydroiodic acid reduction is carried out at 90° C. for 12 h.
8. The method for preparing a continuous graphene nanofiber bundle according to claim 1, characterized in that: In the step S4, the graphitization treatment conditions are heating to 3000° C. at a rate of 10° C. / min in an argon flow and maintaining for one hour.
9. A method for preparing a continuous graphene nanofiber bundle, characterized in that: The preparation method comprises the step of immersing in a Lys-Dopa solution after a coagulation bath, and / or the step of twisting a plurality of graphene fibers into bundles before reducing them into graphene fibers.
Citation Information
Cited By
Graphene wet spinning solution, preparation method of graphene wet spinning solution and application of graphene wet spinning solution in graphene fibers
CN121272605A
Graphene wet spinning solution, its preparation method, and its application in graphene fibers
CN121272605B